2011
DOI: 10.1002/pola.24525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of double photoreactions on polycoumarate photomechanics

Abstract: We established a polymerization condition of 3‐hydroxycinnamic acid, 3HCA, having photoreactive units over all the main chains. The polymers showed two types of photoreaction, that is, intramolecular E–Z isomerization and interchain [2 + 2] cycloaddition. Spectroscopic studies showed that the rate of the isomerization was higher than that of the cycloaddition. Although the original fiber was very brittle, the short‐time UV‐irradiation made the fiber softer and more elastic because the chain bending by the isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…The round shape was very stable after the light was turned off. Based on our previous report on a poly( m ‐hydroxycinnamic acid) film,13e one can easily hypothesize that the present bending behavior could be attributed to the formation of a gradient structure by the photoreaction from the cinnamic double bonds into cyclobutane as demonstrated by subsequent IR‐ and UV‐light studies 9a,b. As shown in Figure 3, it was observed that the round shape B gradually recovered to the original shape A when low‐pressure UV light at λ =250 nm was used for poly2C, probably because of cyclobutane rings cleaved by such short wavelength UV light.…”
Section: Properties Of Various Polyesters (See Scheme  For the Synthementioning
confidence: 99%
“…The round shape was very stable after the light was turned off. Based on our previous report on a poly( m ‐hydroxycinnamic acid) film,13e one can easily hypothesize that the present bending behavior could be attributed to the formation of a gradient structure by the photoreaction from the cinnamic double bonds into cyclobutane as demonstrated by subsequent IR‐ and UV‐light studies 9a,b. As shown in Figure 3, it was observed that the round shape B gradually recovered to the original shape A when low‐pressure UV light at λ =250 nm was used for poly2C, probably because of cyclobutane rings cleaved by such short wavelength UV light.…”
Section: Properties Of Various Polyesters (See Scheme  For the Synthementioning
confidence: 99%
“…The size change can be derived from the interchain distance controlled by photoirradiation. The ultraviolet light was irradiated to the surface of P3HCA film which was more easily processed than other homopolymers prepared in this research, to induce the photobending behavior . Since T g of P3HCA was around 120 °C, the film was a kind of hard plastic at room temperature, and the photobending speed was slow.…”
Section: Polyestersmentioning
confidence: 99%
“…The ultraviolet light was irradiated to the surface of P3HCA film which was more easily processed than other homopolymers prepared in this research, to induce the photobending behavior. 73 Since T g of P3HCA was around 120 °C, the film was a kind of hard plastic at room temperature, and the photobending speed was slow. If the T g was decreased, the photobending should be accelerated.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Since cinnamic acid and its derivates show the well known cis-trans isomerization and inter-and intramolecular [2+2] cycloaddition with UV irradiation, [20][21][22][23][24] the photoreactivities of the PCL-co-PDHCA copolymers were examined by UV-visible spectra in DMF solutions. Figure 4 shows the changes in the absorption spectra of PCL-co-PDHCA26 with various irradiation times during UV irradiation at λ=302 nm.…”
Section: Photoreactivitymentioning
confidence: 99%